DEVELOPMENT OF A SMART KOS METER PROTOTYPE FOR RECORDING ELECTRICITY AND WATER BILLS BASED ON IoT - Hilda Ashari; Dyah Vitalocca; Hamidah Hamris (Jurnal Media Elektrik, 2024)
This research is a development research that aims to: (1) produce prototypes in the form of hardware and software smart kos meter tools for recording electricity and water bills based on IoT and (2) to find out the results of hardware functionality testing, application testing and testing the effectiveness of the smart cost meter prototype tool. IoT-based electricity and water bill logger. The research used is Research and Development (R&D) which is useful for improving and producing a product. The development model used in this research is a prototype development model. The development procedure consists of 4 steps, namely Requirements Analysis, Building a prototype, Coding the System, Testing and Evaluating the System. The results of this study are an analysis of the results of the hardware functionality test with the percentage seen being 100%, the application test results getting a percentage of 100% and the results of testing the performance of the tool by measuring the overall effectiveness of the sensor readings is 93%. Suggestions for further development is that this tool can make more accurate measurements so that the effectiveness of the tool is better, it can be done using two microcontrollers so that the sensor reading program can run well. Then use a digital sensor with more complete measurement data so that sensor accuracy and product effectiveness can be achieved.